Analysis of the surface hardness of niobium carbide coatings deposited on commercially pure titanium and Ti-6Al-7Nb alloy implant materials using the glow discharge plasma technique - Haitham T. Al Qaysi 1, Thekra I. Hamad 2, Thair L. Al Zubaidy 3 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
To enhance the properties of titanium and its alloys for implant applications, NbC thin films were deposited on commercially pure titanium and Ti-6Al-7Nb specimens using a low-temperature plasma glow discharge technique with argon gas and C2H2 as a carbon source. Vicker’s hardness tests were conducted, revealing significantly increased hardness in the coated samples, a finding supported by statistical analysis. This increased surface hardness will potentially improve the wear resistance and load-bearing capabilities, which are essential factors for dental and orthopedic implants. The study aligns with previous research on NbC’s properties, positioning it as a promising material for dental implants. Importantly, the study underscores the reliability of the coating technique for implant surface modification.